2019
DOI: 10.1016/j.jbiomech.2019.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Foot strike pattern, step rate, and trunk posture combined gait modifications to reduce impact loading during running

Abstract: Elevated impact loading can be detrimental to runners as it has been linked to the increased risk of tibial stress fracture and plantar fasciitis. The objective of this study was to investigate the combined effects of foot strike pattern, step rate, and anterior trunk lean gait modifications on impact loading in runners. Nineteen healthy runners performed 12 separate gait modification trials involving: three foot strike patterns (rearfoot, midfoot, and forefoot strike), two step rates (natural and 10% increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 57 publications
1
53
1
Order By: Relevance
“…This subset of individuals also demonstrated the greatest increase in cadence and greatest reduction in AVLR on both limbs (31%) at the post-intervention data collection (T2). Our observation is in agreement with Huang et al, who demonstrated that healthy individuals transitioning to a NRFS combined with increased cadence achieved greater reductions in AVLR than FSP manipulation alone (Huang et al, 2019). Overall, we achieved favorable reductions in AVLR in those with knee complaints with a NRFS transition using an instrumented sock.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This subset of individuals also demonstrated the greatest increase in cadence and greatest reduction in AVLR on both limbs (31%) at the post-intervention data collection (T2). Our observation is in agreement with Huang et al, who demonstrated that healthy individuals transitioning to a NRFS combined with increased cadence achieved greater reductions in AVLR than FSP manipulation alone (Huang et al, 2019). Overall, we achieved favorable reductions in AVLR in those with knee complaints with a NRFS transition using an instrumented sock.…”
Section: Discussionsupporting
confidence: 92%
“…In further support of our hypotheses, cadence increased 2.8% from initial (T1) to post-intervention (T2), but this increase was not maintained at follow-up (T3) ( Table 3, Supplementary Material 4). A cadence increase of 5-10% has been shown to reduce energy absorption of the lower-extremities (Heiderscheit et al, 2011) and reduce ground reaction forces during running (Schubert et al, 2014;Huang et al, 2019;Futrell et al, 2020). Furthermore, it has been reported to be more natural and easier to transition FSP using a combined gait modification involving a NRFS and increased cadence than to transition using an isolated gait modification of NRFS alone (Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In running, almost all variables are modifiable, but some variables are likely easier and more directly to modify. It is, for example, easier to transfer to a forefoot strike pattern when the step rate can be increased at the same time rather than trying to adopt a forefoot strike while keeping the step rate at the baseline level (Huang et al, 2019).…”
Section: Which Running Technique Components Should Be Measured and Momentioning
confidence: 99%